THE ANTIBACTERIAL ACTIVITY OF SOLID SOAP CONTAINING LEMONGRASS (Cymbopogon nardus L.) ETHANOLIC EXTRACT AGAINTS Staphylococcus aureus - Ratih Purwanti; Kenanga Arum Juniarsih; Cut Novrita Rizki (Jurnal Biologi Sains dan Kependidikan, 2021)
The antiseptic soap is a soap that has the ability to kill bacteria better than ordinary soap. To increase the antibacterial activity of soap, synthetic chemicals are generally added (TCC and TCS) which have a negative impact on health and the environment. Natural ingredient that can be used as an antibacterial in antiseptic soap is Lemongrass (Cymbopogon nardus L.). Lemongrass contains essential oil that can inhibit the growth of Staphyloccoccus aureus bacteria. This study aims to make a solid bath soap formulation with various concentration of Lemongrass ethanolic extract, namely Formula I (1%), Formula II (5%), Formula III (10 %). The formulation of bath soap without extract (F0) was used as a negative control. This research is an experimental study with a One Shot Case Study design. The examinations carried out were high foam and antibacterial activity by the well method. The results showed that the preparation of solid bath soap with Lemongrass (Cymbopogon nardus L) ethanolic extract at F0, F1(1%), F2(5%) and F3 (10%) showed antibacterial activity. The diameters of the inhibition zones at F0, F1, F2 and F3 were 1.11mm, 1.70mm, 1.11mm, and 1.02mm, respectively. The height of the soap foam obtained at F0, F1, F2 and F3 respectively was 6.5 cm, 5.6 cm, 5.3 cm and 5 cm. The most effective soap formulation and has the potential to be developed as an antiseptic soap is F1 with an extract concentration 1%. The height of the soap foam in F1 produced was 5.6 cm and the bacteriostatic inhibition zone was 1.7 mm.